Konstitusi dan Struktur Kekuasaan Negara - Aisah Aisah; Halisah Halisah; Nor Yelly; Utin Dila Mantajai; Surya Sukti (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The constitution is a fundamental foundation in the administration of a state, functioning as the supreme law as well as a guideline in regulating power and national life. This article aims to examine the definition of the constitution, its objectives, functions, and scope, as well as its implementation in the Indonesian constitutional system through the 1945 Constitution of the Republic of Indonesia. The method used is library research with a descriptive qualitative approach. The results show that the constitution does not only have a juridical dimension but also philosophical and ethical dimensions, as it contains fundamental values that guide the state toward common goals, as reflected in the thought of Al-Farabi. The 1945 Constitution as Indonesia’s constitution is dynamic and has undergone amendments to strengthen democratic principles, human rights protection, and the system of checks and balances. Furthermore, the separation of powers into legislative, executive, and judicial branches, rooted in the ideas of Montesquieu, serves as an important mechanism to prevent the concentration of power. Therefore, the constitution and a balanced structure of power play a crucial role in establishing a democratic, just, and law-based state.